STUDENTS’ INTERACTION IN COMPUTER MEDIATED LEARNING: ANALYSIS OF PRACTICAL INQUIRY MODEL - Lasito; Husam; Handayani , Magpika (LPPM STBA Pontianak, 2023)
Students’ collaboration is essential for the construction of effective,deep, and reflective learning. In the context of computer-mediated learning, students’ collaboration was facilitated by discussion forum. While discussion forum is used among distanced learners, there is still lack of knowledge on what really happens when students participate in the discussion forum. This study shed lights on students’ engagement in three discussion forums of two language skill courses (Speaking 1 and Writing 1) conducted asynchronously. The engagement was measured from (i) students’ posts or comments to see how much students’ participation in the forum, (ii) engagement patterns they formed, and (iii) how such collaboration reflected the phases of practical inquiry in online-mediated learning. Results showed that during online asynchronous seminars, students’ participation was minimal, and teachers’ posts were prevalent, with posts confirming students’ answers. This type of interaction, in turns, resulting in a one-way serial monologue – students did not response to each other posts. Analysis on practical inquiry model also confirmed the findings that students’ engagements were in the level of triggering event by which students only responded to the teacher’s thread and did not respond to each other posts. Students’ exchange of information was not negotiated, thus not allowing students to move forwards to integration and resolution phases. The findings were linked with the tasks set out by the teachers in both courses.